Registration of Intellectual Property Rights of Thengul Ndadari Batik Motifs Based on Preservation of Dance Art - Indana, Rifaatul (Journal of Islamic Economy and Community Engagement, 2023)
Dolokgede, Tambakrejo village located in Bojonegoro Regency has potential property art. One of the business opportunities that Bojonegoro community has begun to develop is batik, but there are still only a few people have batik character, they only make it without knowing the meaning of the resulting motif. The motifs that are widely used in batik are imagines plant and flower. During this time the community is very worried that there will be attention, extinction, appreciation from others for the batik motifs that have been produced. There for the Disbudpar and Uin Sunan Kalijaga service team asked for assistance to support the assistance of intellectual property rights on batik motifs produced by Dolokgede through the Director General Property Rights. So that it can foster the entrepreneurial spirit of the village community marked by the village communitu. Which produces written batik based on dance art and distributes tourism areas, therefore the tourist area will facilitate written batik produced by the people of Dolokgede Village.